Level of Practicality and Effectiveness of Practicum Guidelines in The Molecular Genetics Course for Students of Biology Undergraduate Study Programs - Novira, Aulya; Jumadi, Oslan; Ali, Alimuddin; Hartono, Hartono (Biology Teaching and Learning, 2023)
Abstract. This type of research is Research and Development (R&D) which aims to determine the level of practicality, and effectiveness of guided inquiry-based molecular genetics guides. The research design uses the ADDIE development model, namely Analyze, Design, Develop, Implement, and Evaluate. The subjects of this research were Lecturers of Biology Department of Makassar State University, and Students. The instrument to test the validity uses a questionnaire sheet validated by an expert validator, to test the practicality of giving a student response questionnaire, lecturer response, and product implementation sheet, and test the effectiveness of multiple choice questions to test student learning outcomes. The data from this study showed that the development of this practicum guide was categorized as practical because the data obtained were in the interval 4 ≤ IO ≤ 5. The effectiveness test used T-Test analysis (Paired Sample Test). From the data analysis, it is obtained that the use of molecular genetics practicum guides is effective in increasing knowledge related to DNA isolation, PCR, and electrophoresis material in practicum activities after being given molecular genetics guides. It can be seen that the significance of p = 0.000 <0.01, meaning that the results obtained are very significant, it can be concluded that the developed guide shows effective on improving student cognitive learning outcomes.Keywords: practicum guide, molecular genetics, guided inquiry, practicality test, effectiveness test